Perbaikan Teknologi Proses dan Manajemen di UKM Smish Cake Kabupaten Jember - Elly Kurniawati; Wahyu Suryaningsih; Titik Budiati; Agung Wahyono; Annisa'u Choirun (Indonesian Journal Publisher, 2025)
Small micro and enterprises (SMEs) are an important part of improving the people's economy, one of the SMEs that produces various types of cakes or snacks including sweet bread, banana bread and cakes is SME SMISH Sempolan Village, Silo District, Jember Regency. In the production process, SMISH SME had problems regarding the production capacity and quality of sweet bread and banana bread products which are still low, and they do not yet have P-IRT. Based on this, community empowerment service (PPM) was carried out with the following objectives: (1). Improving process technology to increase production capacity and bread quality. (2) improve production management. The method of community service activities includes the stages of observation, coordination, counseling on improving processing technology; improving production management with counseling and training on GMP and SSOP in implementation during production. After carrying out the dedication process, it can be shown that SME SMISH CAKE has made improvements in the quality of sweet bread and banana bread to be better, production capacity has increased by around 30-35%, increased knowledge of GMP, SSOP and production management, increased marketing reach and can sell online and get P-IRT production permit.